Efficient Compost Fertilizer with Addition of Fatty Acid Results of Used Cooking Oil Saponification Reaction - Ardiyanti, Aprilia Dewi; Adhitama, Lukman; Wahyutiyani, Rina (Proceeding International Conference on Science and Engineering, 2020)
The development of the times accompanied by technological developments have brought humans to the Post Modern era. The industry is growing rapidly in all lines, both from the sectors of production of goods, textiles, materials and even penetrated the food sector. Food innovations have sprung up rapidly and creating waste. One of them is vegetable and fruit waste. However, this waste can be processed into compost because the content of Nitrogen, Phospor and Potassium (NPK) which is a basic need for plants to carry out photosynthesis. Processing of vegetable waste into compost is done by adding EM4, molasses and remaining rice washing water. Fermentation is carried out for four weeks to produce compost. Other waste arises from the food industry which produces foodstuffs by frying. Used cooking oil left over from the frying pan is often discharged into the environment to cause pollution. This can be more severe if the disposal is in residential areas. Saponification reaction using natrium hydroxide (NaOH) can separate glycerol and fatty acids from used cooking oil. Fatty acids from the separation of solid waste cooking oil can purify the NPK content in compost, so that when mixed with compost an efficient compost can be produced and has a high NPK percentage. The purpose of this study is to obtain accurate information from literature studies to determine the percentage of NPK in compost after adding fatty acids from used cooking oil.